Propofol restores TRPV1 sensitivity via a TRPA1‐, nitric oxide synthase‐dependent activation of PKCε. Issue 4 (11th June 2015) - Sinharoy, Pritam; Zhang, Hongyu; Sinha, Sayantani; Prudner, Bethany C.; Bratz, Ian N.; Damron, Derek S.
Abstract: We previously demonstrated that the intravenous anesthetic, propofol, restores the sensitivity of transient receptor potential vanilloid channel subtype‐1 (TRPV1) receptors via a protein kinase C epsilon (PKC ε )‐dependent and transient receptor potential ankyrin channel subtype‐1 (TRPA1)‐dependent pathway in sensory neurons. The extent to which the two pathways are directly linked or operating in parallel has not been determined. Using a molecular approach, our objectives of the current study were to confirm that TRPA1 activation directly results in PKC ε activation and to elucidate the cellular mechanism by which this occurs. F‐11 cells were transfected with complimentary DNA (cDNA) for TRPV1 only or both TRPV1 and TRPA1. Intracellular Ca 2+ concentration was measured in individual cells via fluorescence microscopy. An immunoblot analysis of the total and phosphorylated forms of PKC ε, nitric oxide synthase (nNOS), and TRPV1 was also performed. In F‐11 cells containing both channels, PKC ε inhibition prevented the propofol‐ and allyl isothiocyanate (AITC)‐induced restoration of TRPV1 sensitivity to agonist stimulation as well as increased phosphorylation of PKC ε and TRPV1. In cells containing TRPV1 only, neither agonist induced PKC ε or TRPV1 phosphorylation. Moreover, NOS inhibition blocked propofol‐and AITC‐induced restoration of TRPV1 sensitivity and PKC ε phosphorylation, and PKC ε inhibition prevented the nitric oxide donor, SNAP, from restoring TRPV1 sensitivity. Also, propofol‐and AITC‐induced phosphorylation of nNOS and nitric oxide (NO) production were blocked with the TRPA1‐antagonist, HC‐030031. These data indicate that the AITC‐ and propofol‐induced restoration of TRPV1 sensitivity is mediated by a TRPA1‐dependent, nitric oxide synthase‐dependent activation of PKC ε .